ANALYSIS OF FACTORS AFFECTING POVERTY IN ISLAMIC PERSPECTIVE EAST JAVA - Arikha Nur Adhilla; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The purpose of economic development in Islam is to achieve falah (happiness in the world and the hereafter). One of the main indicators of the success of economic development is the low level of poverty. Poverty is a complex problem that needed to solve. Several factors that influence poverty are economic growth and district/ city minimum wage. This research aims to know the influence of economic growth and district/city minimum wage on the poverty level in East Java in 2012-2016. The approach used is the quantitive research with regression analysis of the fixed-effect model (FEM) panel data. The result of the t-test in this research indicates that both economic growth and district/city minimum wage has a significant negative effect on poverty. Simultaneously, the two variables have a significant effect on poverty in East Java in 2012-2016Keywords: Economic Growth, Minimum Wage, Poverty, Islamic Macro EconomicREFFERENCE Ahyani, Shidqi. (2016). Kemiskinan dalam perspektif al-qur’an dan solusinya dalam pandangan Islam (Studi pemikiran Sa’ad Ibrahim dan Yusuf Qardhawi tentang penanggulangan kemiskinan). Jurnal Kariman, 4(1), 43-64.Harun, Salman. (1999). Mutiara Al-Qur’an: Aktualisasi pesan Al-Qur’an dalam Kehidupan. Jakarta: Logos.Huda, Nurul dkk. (2008). Ekonomi makro Islam: Pendekatan teoritis, edisi pertama. Jakarta: Kencana Prenada Media Grup.Ilmi, Syaiful. (2017). Konsep pengentasan kemiskinan perspektif Islam. Jurnal Al-Maslahah, 13(1), 67-84. DOI: https://doi.org/10.24260/almaslahah.v13i1.918Kuncoro, Mudrajad. (2011). Metode kuantitatif teori dan aplikasi untuk bisnis dan ekonomi. Yogyakarta: Penerbit dan Percetakan Sekolah Tinggi Ilmu Manajemen YKPN.Mannan, Abdul. (Tanpa Tahun). Teori dan praktik ekonomi Islam. Terjemahan oleh M. Nastangin 1997. Yogyakarta: PT. Dana Bhakti Wakaf.Naf’an. (2014). Ekonomi makro: Tinjauan ekonomi syariah, cetakan pertama. Yogyakarta: Graha Ilmu.Ridwan, Murtadho. (2013). Standar upah pekerja menurut sistem ekonomi Islam. Jurnal Equilibrium, 1(2), 241-257.Riskiansyah, M. (2017). Pengaruh upah karyawan terhadap kinerja karyawan bagian lapangan pada toko classic dalam perspektif Islam. Skripsi tidak diterbitkan. Palembang: UIN Raden Fatah.Simanjuntak, Payaman J. (1985). Pengantar ekonomi sumber daya manusia. Jakarta: LPFE Universitas Indonesia.Suryawati, Chriswardani. (2005). Memahami kemiskinan secara multidimensional. JurnalManajemen Pelayanan Kesehatan, 8(3), 121-129.Todaro, Michael P. (2000). Pembangunan ekonomi di dunia ketiga, edisi kedelapan,terjemahan oleh Haris Munandar. Jakarta: Penerbit Erlangga.